Social challenges of building education for Young People, Adults and the Elderly (EJAí): Reflections on Brazilian Legislation and Education (Research, Society and Development, 2024)
The aim of this article is to reflect on the education of young people, adults and the elderly today and how Brazilian legislation should guarantee adequate education for this public. Thus, it reads official documents to understand the trajectory of public policies aimed at adults in Brazil. To this end, we read theoretical contributions such as Carneiro, Souza, Sales, Freire, the Law of Guidelines and Bases (LDB) and the Brazilian Constitution of 1988.